Association of methylenetetrahydrofolate reductase gene variant C677T and folate levels in non-syndromic cleft lip/palate among Sindhi, Pakistani population - Effendi, Sadia; Memon , Samreen; Khidri, Feriha Fatima; Waryah , Ali Muhammad (Journal of the Pakistan Medical Association, 2023)
The objectives of this study were to determine the association of methylenetetrahydrofolate reductase (MTHFR) gene variant C677T with non-syndromic cleft lip/palate (NSCLP) in Pakistani population and compare the maternal serum folic acid levels in NSCLP-affected and healthy group. A comparative cross sectional study was conducted between 2017 and 2019 at Liaquat University of Medical and Health Sciences, Jamshoro. Sixty mother-infant dyads were recruited (n = 120), including NSCLP-affected and healthy infants along with their mothers. The MTHFR C677T variant exhibited significant association with NSCLP in dominant and over-dominant models. No differences in maternal serum folic acid levels were observed between both the groups; however, the folic acid intake during pre-conception period was associated with decreased risk for NSCLP. Our study suggested that MTHFR 677 CT genotype was related with decreased risk for NSCLP in Sindhi, Pakistani, population. Pre-conception folic acid may decrease the risk for oral clefts.